Bedside Teaching in Neurology - Dewey, Jeffrey J.; Cho, Tracey A. (Seminars in Neurology, 2018)
The patient's bedside offers an ideal venue for teaching the art of clinical neurology and modeling humanism and professionalism. However, bedside teaching is underutilized in modern medical education, despite evidence that learners desire more. Logistical challenges and lack of teacher confidence are commonly cited reasons, but both can be mitigated with a deliberate approach and sufficient experience. Well-executed bedside teaching can provide lasting lessons for learners while enhancing the patient experience, without affecting the efficiency or quality care delivery. In this review, we discuss the theory and evidence to support the use of bedside teaching, and subsequently delineate a framework for designing and executing effective bedside teaching in neurology.
Keywords: bedside teaching; medical education; learning theory; adult learner